Capital Market Reactions to The Covid 19 Pandemic - Umayi Ananda, Woro; Gursida, Hari; Indrayono, Yohanes (Journal of World Science, 2023)
This study aims to determine and analyze the capital market's reaction to the Covid 19 Pandemic in biotechnology companies listed on the Nasdaq. The method used in this study uses a type of quantitative method. This study uses an event study. The sampling method in this study was carried out using a non-probability random sampling approach. The announcement of the COVID-19 pandemic by the WHO and the commitment to produce a COVID-19 vaccine have had a significant impact on abnormal stock returns and trading volume activities of biotech companies listed on the NASDAQ stock market. However, there is no significant effect on the liquidity of biotech company stocks. In addition, the announcement of the COVID-19 pandemic also affected the volatility of biotech company stocks. In contrast, the announcement of a commitment to producing a COVID-19 vaccine did not significantly impact the volatility of biotech company stocks. So, it shows that the NASDAQ stock market reacts sensitively to announcements about the COVID-19 pandemic and efforts to produce COVID-19 vaccines by biotech companies. This shows that the COVID-19 pandemic has significantly impacted the stock market, especially in the biotechnology sector. The event study approach is used to test the market with a semi-strong form of market efficiency by demonstrating that the stock price reflects all published information (all publicly available information).